Factors That Influence The Application Of Accounting Conservatism In Finance Reports (Empirical Study In Manufacturing Companies Which Are Listed In The Jakarta Stock Exchange Period 2011-2014) - Rega Chairunnisya; Afrizal Afrizal; Wirmie Eka Putra (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2017)
This research has an aim to empirically prove the influence of a company's broad size, audit committee, growth opportunities, firm size, firm risk, capital intensity, and leverage on accounting conservatism. The research sample are the manufacturing companies listed on the Indonesia Stock Exchange (BEI) in the period of 2011-2014 which was chosen by purposive sampling and 28 companies in criteria were obtained.This research used the multiple linear regression for data analysis. The results of the research showed that (1) broad size, audit committee, growth opportunities, firm size, firm risk, capital intensity, and leverage had a simultaneous influence to accounting conservatism, (2) broad size, firm size, and firm risk had a partial influence to accounting conservatism, (3) audit committee, growth opportunities, capital intensity, and leverage do not have partial influence to accounting conservatism.Keywords: Accounting Conservatism, Audit Committee, Broad Size, Capital Intensity, Firm Size, Firm Risk, Growth Opportunities, Leverage